Sinergitas Peran Kepolisian dan Masyarakat dalam Menanggulangi Balapan Liar di Kota Padang - Winaldo Winaldo; Fitriati Fitriati; Bisma Putra Pratama (UNES Law Review, 2023)
Article 115 of Law Number 22 of 2009 concerning Road Traffic and Transportation (UU LLAJ) regulates the prohibition of illegal racing. This research is an empirical juridical research. The handling of wild races in the City of Padang by the Padang Traffic Police with synergy between the Padang Traffic Police and the Community in tackling illegal racing in the City of Padang is carried out preventively with community leaders by conducting outreach to schools, in print and electronic media. Making banners on the streets, broadcasting on the radio, social media such as Instagram by involving respected community leaders in the illegal racing area. Patrol activities to create conditions at night with people who carry out patrols at night. Patrols are carried out by walking along streets that have the potential to be used as places for speeding. Supervision at posts that are prone to wild racing with the local community. Repsentially, the synergy with the community is that the community helps officers search for illegal racers. The obstacle in the synergy between the Padang Traffic Police and the community in tackling illegal racing in the city of Padang is that there are still people who do not want to assist police officers in catching and raiding illegal racers. Because the large number of illegal racers who have been caught in cases of illegal racing in the city of Padang is not proportional to the number of police personnel who are on night picket duty. The level of legal awareness of the people of Padang City to comply with traffic rules is very low. Society that is less corporative by becoming spectators of wild racing, there are workshops and motorcycle gangs that provoke teenagers, there is betting (gambling), lack of attention and supervision of parents towards children, lack of facilities and infrastructure, and lack of funds to channel the hobby of racing.